Poverty and social exclusion in India (New Delhi, 2013)
Despite India's record of rapid economic growth and poverty reduction over recent decades, rising inequality in the country has been a subject of concern among policymakers, academics, and activists alike. Poverty and Social Exclusion in India focuses on social exclusion, which has its roots in India's historical divisions along lines of caste, tribe, and the excluded sex, that is, women. These inequalities are structural in nature and have kept entire groups trapped, unable to take advantage of opportunities that economic growth offers. Culturally rooted systems perpetuate inequality, and, rather than a culture of poverty that afflicts disadvantaged groups, it is these inequality traps that prevent such groups from breaking out. Combining rigorous quantitative research with a discussion of underlying processes, this book finds that exclusion can be explained by inequalities in opportunities, access to markets, and in voice and agency.
Keywords: Poverty-India, Economic history-India, Poverty